Tunable double-Weyl Fermion semimetal state in the SrSi(2) materials class - Singh, Bahadur (Sci Rep, 2018)
We discuss first-principles topological electronic structure of noncentrosymmetric SrSi(2) materials class based on the hybrid exchange-correlation functional. Topological phase diagram of SrSi(2) is mapped out as a function of the lattice constant with focus on the semimetal order. A tunable double-Weyl Fermion state in Sr(1−x)Ca(x)Si(2) and Sr(1−x)Ba(x)Si(2) alloys is identified. Ca doping in SrSi(2) is shown to yield a double-Weyl semimetal with a large Fermi arc length, while Ba doping leads to a transition from the topological semimetal to a gapped insulator state. Our study indicates that SrSi(2) materials family could provide an interesting platform for accessing the unique topological properties of Weyl semimetals.